CENTRAL AORTIC PRESSURE AND CARDIOVASCULAR RISK FACTORS ASSESSMENT IN STUDENTS AS A PART OF THE YOUTH SCREENING IMPROVEMENT - M. E. Evsevyeva; M. V. Eryomin; M. V. Rostovtseva; O. V. Sergeeva (Российский кардиологический журнал, 2015)
Aim. To study the main risk factors on representative group of first-year students of StSMU during their screening, and on pilot group of students to study possible ways of influencing on these factors on CBP and its augmentation index.Material and methods. Totally 1351 first-year students screened for risk factors as inheritance of early onset of CVD, overweight, PH (prehypertension)/AH, smoking, chronic infectiousand immunity-related inflammations, wrong diet, hypodynamia, low stress resistibility, and for some of them — dyslipidemia and hyperglycemia (capillar test). In 80 patients, taken their risk factors, we assessed CBP and its augmentation index with diagnostical complex BPLab Vasotens Office (LLC “Piotr Telegin”, Nizhniy Novgorod).Results. Among first-year students with PH/AH overweight were each tenth, inheritance or focal infections — almost in each fifth. Wrong diet, hypodynamia and low stress resistibility are found in each fourth-fifth of enrolled in university. Absence of risk factors was found only in one fifth of first-graders. Most of them have two and more risk factors. Having these factors students usually had an increase of systolic, mean and pulse pressure in aorta, and augmentation index of central pulse pressure. Significantly more common in them is to find systemic and isolated central PH/AH.Conclusion. Regardless of young age and short anamnesis of adverse factors, students have preclinical, however quite clear damage of target organs such as vessel remodeling, including large vessels. It is necessary to implement broader into the centers of student healthcare and outpatient institutions the methods of CBP assessment as an office procedure with the aim of earlier vessel remodeling relevance during screening events with the aim for risk groups formation and control of efficacy of prevention procedures in such risk groups.